THE EFFECTIVENESS OF THE SIDOARJO FINANCIAL INFORMATION SYSTEM (SIKSDA) IN IMPROVING REGIONAL FINANCIAL MANAGEMENT PERFORMANCE AT THE REGIONAL FINANCIAL AND ASSET MANAGEMENT AGENCY OF SIDOARJO REGENCY - Anggraeni, Wiwik; Choiriyah, Ilmi Usrotin (PT ANTIS INTERNATIONAL PUBLISHER, 2025)
Objective: This study aims to evaluate the effectiveness of the implementation of the Sidoarjo Financial Information System (SIKSDA) in improving the performance of regional financial management at the Regional Financial and Asset Management Agency (BPKAD) of Sidoarjo Regency. Method: The research employed a qualitative descriptive approach, with data collected through in-depth interviews, observations, and documentation studies, and the analysis was guided by Richard M. Steers' theory of organizational effectiveness, which emphasizes goal achievement, integration, and adaptation. Results: The findings indicate that SIKSDA has enhanced the financial reporting process by improving speed and accuracy, ensuring timely achievement of budget targets, facilitating integration with tax, procurement, and asset systems, and demonstrating strong adaptability to regulatory changes through regular training, system maintenance, and risk mitigation. Novelty: This study highlights the role of SIKSDA as a model for effective digital-based financial governance at the local government level, showing how integrated financial information systems not only increase efficiency and accountability but also provide strategic adaptability, offering insights and practical implications for other regions seeking to strengthen their financial management practices.